AKTIVITAS ANTIJAMUR MINYAK ATSIRI DAUN KETEPENG CINA (Senna alata (L.) Roxb) TERHADAP JAMUR OPORTUNISTIK - Nilda Lely (Jurnal Penelitian Farmasi Indonesia, 2016)
A research of antifungal activity from the essential oil of Senna alata (L.) Roxb against fungus that causes opportunistic infections.This research was conducted by agar diffusion method to test fungus Aspergillus fumigatus, Candida albicans and Penicillium marneffei. The result of water vapor distillation of the leaves Senna alata obtained rendemen by 0,125%. The research had done in variation concentrastions respectively 25%, 20%, 15% ,10% and 5% obtained from observations of the average diameter of inhibitions on fungus Aspergillus fumigatus by 17.48 mm, 15.18 mm, 13.28 mm, 11.33 mm and 9.80 mm, Candida albicans by 12.86 mm and the Penicillium marneffei 19.46 mm, 16.06 mm, 14.48 mm, 13.16 mm, 12 .23 mm. Analyzed for essential oil constituents by GCMS. The quantitatively significant constituents of the leaf essential oil of Senna alata (L.) Roxb were 1,8 cineole (48.97%), α- pinene (24.96%), 1,4 cyclohexadine (9.53%), Trans- β- ocimene (7.48%) and P-cymene (4.53%).